Policing crisis in Northern Ireland, Afghanistan, and Iraq - Boyd, Gavin (Routledge international handbook of policing crises and emergencies, 2025)
August 1969 marked a crisis point for the Royal Ulster Constabulary (RUC) when, after several months of political and intercommunal conflict, it was unable to cope with the associated street-level violence and the military were deployed, taking over responsibility for maintaining security and public order. A subsequent review of the police and policing (Hunt Report 1970) made recommendations that the RUC should modernise along similar lines as other United Kingdom forces. This, taken with the Royal Commission on the Police (1964), sought to restore public confidence in the police. However, political inertia and the continuing conflict created a political vacuum which did little to settle intercommunal tensions, creating a chaotic social environment in which self-styled ‘community’ defenders emerged prepared to use armed violence in pursuit of their political objectives. These emerging threats drew the military into violent and armed encounters with these groups of ‘community’ defenders. Policing is generally understood to be the police answering calls for assistance from the public, detecting crime, and maintaining order necessary for the normal functioning of society. This ‘ordinary’ or civic policing style is severely tested when regime change is sought by violence and terrorism, creating a crisis for policing and forcing the state to adopt extra security policing techniques and emergency powers. This chapter traces the development of the RUC policing style as it sought to re-establish its reputation as an ‘ordinary’ police service whilst simultaneously leading the state effort to counter-terrorism and political violence. This chapter draws on experiences of former RUC officers to explore how policing in Northern Ireland responded to the emergence of political violence, before reflecting on how this response compares with policing in Afghanistan and Iraq.